Development of deformation medelling software on geodetic monitoring network using / Iterative weighted similaritary transformation / (IWST) / Muhammad Taufik Ismail - Ismail, Muhammad Taufik (2018)
Deformation survey is an important activity in engineering surveys in order to determine the safety of the structure. Therefore, the deformation detection in the analysis of deformation is a crucial part that needs to be taken care of in deformation survey. Iterative Weighted Similarity Transformation (IWST) is the robust estimation method in deformation analysis. While the deformation modelling is a method to determine the pattern of deformation occurs on monitoring network. In this study, the process begins by using existing program network adjustment and deformation detection acquired from previous study and a new program based on deformation modelling is developed using MATLAB software throughout this study. The reliability of the program was evaluated using two sets of data which are the data from previous studies and observed data that collected during this study was conducted. The data consists of the geodetic monitoring network information, including coordinate, distance, angle and azimuth in two epochs for both data sets. Each set of data verified statistically through the program. The outcomes from this study are the results produced by the program used consist of adjustment result, deformation detection result and deformation modelling result tabulate in respect of each data sets. The results of deformation modelling consist of the model tested, the global test status which either passed or failed and deformation parameter. The determination of the best model will be based on passing the global test and the least parameter if there is more than one model passing the test. Based on previous data, the result of deformation modelling successfully determine the same model used in previous study as the best model. Meanwhile the observed data used in this study happened to occur two model passing the test and allowing the consideration of the second condition. The result of the program verified the reliability of developed program and ensure the program is succeeding in performing deformation analysis.